Association of osteosarcopenia with physical frailty and cachexia in patients undergoing hemodialysis: the REPnet-HD study - Masakazu Saitoh; Naoto Usui; Sho Kojima; Yoichi Sato; Yoshifumi Abe; Akihiro Sakuyama (Renal Replacement Therapy)
Abstract Aim The association between osteosarcopenia and the development of physical frailty (PF) or cachexia in patients undergoing hemodialysis (HD) remains unclear. This study aimed to investigate the clinical features of osteosarcopenia and assessed its correlation with PF and cachexia in patients undergoing HD. Methods This study is a sub-analysis of the REPnet-HD study, a prospective multicenter observational study involving 110 patients undergoing HD (median age, 66 years; 34% female). Sarcopenia and osteopenia were diagnosed using the Asia Working Group for Sarcopenia 2019 and World Health Organization criteria. Subsequently, we evaluated the associations among osteosarcopenia, PF, and cachexia. Multifrequency bioimpedance analysis was performed to determine the phase angle (PhA). Results On the basis of dentition, 59 (53.6%), 12 (10.9%), and 39 (35.5%) cases were classified as non-sarcopenia, sarcopenia alone, and osteosarcopenia, respectively. The prevalence of cachexia (18.6% versus 41.7% versus 53.8%, P < 0.001) and PF (22.0% versus 58.3% versus 66.7%, P < 0.001) was higher in the osteosarcopenia group. Osteosarcopenia was significantly associated with cachexia (odds ratio [OR] 5.390, 95% confidence interval [CI] 2.158–13.465) and PF (OR 6.805, 95% CI 2.739–16.906) after adjusting for propensity score. The optimal cutoff value for diagnosing osteosarcopenia was a PhA of 4.25° in males (area under the curve [AUC] 0.818, 95% CI 0.606–0.952) and 4.20° in females (AUC 0.779, 95% CI 0.695–0.942). Conclusions Patients with osteosarcopenia undergoing HD exhibited a high risk of PF and cachexia. In addition, our findings suggest that PhA may be a valuable tool for screening osteosarcopenia.